Assessing Nepalese Stock Market Efficiency through P/E Portfolios - Dipendra Karki; Rewan Kumar Dahal (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
The study uses a systematic price/earnings (P/E) strategy portfolio analysis to test the market efficiency on the Nepal Stock Exchange (NEPSE). It employs a multi-stage quantitative process that permits quarterly portfolio rebalancing through updated metrics. It examines 338 portfolios that existed between July 2014 and April 2025 and found that the P/E strategy generated substantial profits through its investment returns. The investment returns show a range between 2.5% and 40.9% for various holding durations, while the average excess return stands at 16.5% above the market benchmark. The research investigates P/E strategy portfolios through Sharpe and Treynor ratio assessments at the NEPSE. The two ratio results show consistent outcomes, which show that systematic quantitative strategies are capable of identifying price discrepancies and provide proof that contradicts the weak-form Efficient Market Hypothesis (EMH). The research shows that P/E ratios, which the public can access, hold valuable information for decision-making systems that investors should consider when developing their investment portfolios. The study’s findings challenge the weak-form EMH while suggesting that behavioral and institutional factors may drive ongoing market anomalies in emerging markets like Nepal.